THE GOTHIC ELEMENTS IN TIM BURTONS (1999) SLEEPY HOLLOW THE HEADLESS HORSEMAN: A LITERARY AND CINEMATIC ASPECT ANALYSIS - Gerardus Majella Adhyanggono Adhyanggono; Fransiska Linda Marcelina (Soegijapranata Catholic University, 2013)
Sleepy Hollow is a film directed by Tim Burton. The story tells about a young policeman Ichabod Crane, who is sent to a village called Sleepy Hollow to investigate a murder case there. At first, he was a person who never believed in supernatural things especially ghost, but after facing the reality of the ghost itself, he becomes very scared, but all he has to do is to find the villain behind the ghost of Headless Horseman. This thesis analyzes the gothic elements that are shown in this film. The theories that are used in this thesis are from film studies, literary and cinematic aspect. In this paper, the pictures from the scenes are also shown to show the evidence of the gothic elements. The theories that are used will also show how they can advocate the gothicness of this film.